1995
DOI: 10.1016/0920-3796(95)90172-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of insulating coatings for liquid metal blankets

Abstract: The submitted manuscript has been authored by a contractor of the U.S. Government I under contract No. W-31-109-ENG-38. I Accordingly, the U. S. Govermnent retains a J nonexclusive, royalty-free license to publish I or reproduce the published form of this J contribution, or allow others to do so, for U. S. Government purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The MHD pressure drop is a critical issue for liquid lithium fusion reactor blankets [1,2]. An electrically insulating coating with oxide ceramics is one of the attractive methods for reducing the MHD pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…The MHD pressure drop is a critical issue for liquid lithium fusion reactor blankets [1,2]. An electrically insulating coating with oxide ceramics is one of the attractive methods for reducing the MHD pressure drop.…”
Section: Introductionmentioning
confidence: 99%
“…An electrical current flowing perpendicular to a magnetic field results in a mechanical force that leads to MHD pressure drop. 2 It has been shown that even thin conducting walls would lead to a high pressure drop under the conditions of the ITER blanket; for example, the pressure drop in a poloidal duct in an inboard blanket segment would reach 8.6 MPa if the conducting liner is 0.1 mm thick. 3 This unacceptably high pressure drop shows the need for electrically insulating coatings in contact with the flowing liquid metal.…”
Section: Purpose Of Insulator Coatingmentioning
confidence: 99%
“…The calculation shows that a perfectly insulating coating on the wall would decrease the pressure drop from 8.6 to 0.22 MPa. 2,3 Even though a very low pressure drop can be achieved with a perfectly insulating coating, in practice it is necessary to know the effect of coating integrity on the insulating characteristics because any and all of the coating methods can yield only coatings with defects such as pinholes, cracks, minute flaws, etc. Further, a pressure drop of 1-2 MPa is acceptable for a liquid-metal blanket in a fusion reactor application.…”
Section: Purpose Of Insulator Coatingmentioning
confidence: 99%
“…Er 2 O 3 coating is one of the promising methods to restrict tritium permeation and magneto hydrodynamic (MHD) effect for advanced breeding blanket systems [2]. Hishinuma et al reported the formation of Er 2 O 3 coating layer on interior surface area of a short quartz tube using metal organic chemical vapor deposition (MOCVD) process as a new technology for broad and complicated shaped area [3]. The blanket system undergoes neutron irradiation during operation, and the Cu 2+ ion irradiation can be a reasonable candidate to simulate neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%